Climate Change and Plant Abiotic Stress Tolerance 2013
DOI: 10.1002/9783527675265.ch19
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Climate Change on MicroRNA Expression in Plants

Abstract: Climate change is an alarming issue of the twenty-first century, and the effect of climate change on plant resources, biodiversity, and global food security is a major concern. For assured food production in the projected climates of 2030 and beyond, it is essential that we understand at the molecular level how plants respond and adapt to higher temperatures, drought, high CO 2 , ozone, and UV-B radiation, which are some of the major stresses that will be associated with the changing climates. In plants, stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 85 publications
(99 reference statements)
0
2
0
Order By: Relevance
“…Some of these include transcription, processing, biogenesis, and RISC incorporation, which can collectively determine the miRNA levels in a tissue and at a stage [ 12 ]. Furthermore, the environmental conditions at different sampling dates, such as heat, ozone, and drought, also affect miRNA expression [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some of these include transcription, processing, biogenesis, and RISC incorporation, which can collectively determine the miRNA levels in a tissue and at a stage [ 12 ]. Furthermore, the environmental conditions at different sampling dates, such as heat, ozone, and drought, also affect miRNA expression [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, post-transcriptional gene regulation is a less understood phenomenon compared to the transcriptional regulation in response to drought. Several recent studies have shown that miRNAs that act as post-transcriptional regulators are regulated by drought and other abiotic stresses revealing a new layer of gene regulation that is very important for adapting to stress conditions (Sunkar et al 2007Ghorecha et al 2013). Furthermore, miRNA regulation differs between drought sensitive and tolerant genotypes under stress (Kulcheski et al 2011).…”
Section: Introductionmentioning
confidence: 99%